Asymmetric sacroiliac joint anatomy in partial lumbosacral transitional variations: Potential impact on clinical testing in sacral dysfunctions. (March 2019) - Mahato, Niladri Kumar
Abstract: Lumbosacral transitional vertebrae (LSTV) anomalies may present as bio-mechanical dysfunctions leading to low back pain (LBP). Unilateral or incomplete/partial LSTVs have been documented to be associated with significant sacroiliac joint (SIJ) joint asymmetries. Objective evaluation of outcomes from routine clinical testing for sacral dysfunctions on these subsets of LSTV cannot be found in the literature. Based on quantitative studies available on LSTV-associated anatomical variations at the SIJ, this study hypothesizes probable outcomes of standard palpatory clinical tests used to evaluate sacral dysfunctions in unilateral LSTV anomalies. Since LSTV is reported in a sizeable percentage in the general population and due to its proposed etiological relationship with LBP, these entities warrant attention in terms of the anatomical bases of related clinical assessments and their outcomes, as proposed in this hypothesis.